2020
DOI: 10.2147/phmt.s229227
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Birth Asphyxia Among Newborns in Referral Hospitals of Amhara National Regional State, Ethiopia</p>

Abstract: Background: Globally, every year, 2.5 million infants die within their first month of life. Birth asphyxia is one of the leading causes in all low-and middle-income countries and the leading single cause of neonatal mortality in Ethiopia. Therefore, the aim of this study was to identify the determinants of birth asphyxia among newborns admitted to neonatal intensive care units (NICU) in Amhara region referral hospitals, Ethiopia. Methods: Facility-based unmatched case-control study was employed from March 1 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
12
2
1
Order By: Relevance
“…Less than or equals to two ANC follow up by the mothers were 4.6 times higher odds of developing asphyxiated newborns than mothers who have more than four ANC follow up. This finding was inconsistent with the study conducted in Ethiopia [ 13 , 23 , 27 ]. This difference may be due to the number of health facilities included in the study and study period.…”
Section: Discussioncontrasting
confidence: 97%
“…Less than or equals to two ANC follow up by the mothers were 4.6 times higher odds of developing asphyxiated newborns than mothers who have more than four ANC follow up. This finding was inconsistent with the study conducted in Ethiopia [ 13 , 23 , 27 ]. This difference may be due to the number of health facilities included in the study and study period.…”
Section: Discussioncontrasting
confidence: 97%
“…Prolonged labor was also observed as a significant risk factor for birth asphyxia (P<0.0001). This was similar to the studies conducted in the past in different parts of the world like Dhaka medical college hospital, Jimma Medical Center Ethiopia, Referral Hospitals of Amhara National Regional State Ethiopia, Nigeria, and from Stockholm and Gotland Sweden [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 89%
“…Anemia in pregnancy is more prevalent in the developing world, where under nutrition and infections are more frequent which complicates pregnancy outcome. However, a study done in Amhara region Ethiopia and Japan indicated that anemia during pregnancy is not a determinant factor for birth asphyxia/low Apgar score [17,28]. This difference could be due to high prevalence of a history of antepartum hemorrhage in this study and difference in study setting.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, by identifying the determinant factors of the low Apgar score the preventive action could be taken to reduce the number of neonatal deaths and morbidity associated with a low Apgar score. Published studies in Ethiopia that identified the determinant factors of the 5th minute Apgar score was limited [11,16,17]. Therefore, this study aimed to identify significant determinant factors of low Apgar scores among newborns in Hawassa city, South Ethiopia (Table 1).…”
Section: Introductionmentioning
confidence: 99%